Optical fiber accelerometer system for structural dynamic monitoring - Antunes, Paulo Fernando da Costa
In this study, the implementation of an optical accelerometer unit based on fiber Bragg gratings, suitable to monitor structures with frequencies up to 45 Hz, is reported. The developed optical system was used to estimate the structure eigenfrequencies of a steel footbridge, with a total length of 300 m, over the Sao Pedro Creek, located at University of Aveiro Campus, in Portugal. The acceleration records measured with this solution are compared with those obtained by traditional commercial electronic devices, revealing a root-mean-square error of 2.53 x 10(-5) G.